EFFECT OF BENZALDEHYDE EXCESS IN THE SYNTHESIS OF LR-2 AND CYTOTOXIC ACTIVITY OF LR-2 AGAINTS HeLa CELL - Ritmaleni, Ritmaleni; Arifin, Muhammad Fajar; Laksmiani, Ni Putu Linda; ., Rumiyati; ., Sismindari (INDONESIAN JOURNAL OF PHARMACY, 2012)
LR-2(4-phenyl-3,4-dihydro-indeno[2â,1â]pyramidine-2(1H)- thione;Â  LeniÂ  RitmaleniÂ  2),Â  whichÂ  designedÂ  andÂ  assumedÂ  toÂ  have biologicallyÂ  activityÂ  asÂ  anticancer,Â  hasÂ  beenÂ  successfully synthesizedÂ  byÂ  usingÂ  theÂ  BiginelliÂ  reaction.Â  ThisÂ  researchÂ  was aimedÂ  toÂ  investigateÂ  theÂ  effectÂ  ofÂ  benzaldehydeÂ  excessÂ  inÂ  the synthesisÂ  ofÂ  LR-2Â  andÂ  toÂ  evaluateÂ  theÂ  cytotoxicÂ  activityÂ  ofÂ  LR-2against HeLa cancer cell lines. The synthesis was done by reacting benzaldehyde, 2-indanone and togetherÂ  with thiourea at one time asÂ  saidÂ  asÂ  oneÂ  potÂ  reactionÂ  syntheticÂ  methodologyÂ  andÂ  the reaction was acid catalysed. The mole equivalent of benzaldehyde wasÂ  inÂ  excessÂ  compareÂ  toÂ  others.Â  TheÂ  effectÂ  ofÂ  benzaldehydeÂ  in excess is the higher the mole of benzaldehyde, the lower the yield ofÂ  LR-2.Â  TheÂ  cytotoxicityÂ  ofÂ  LR-2Â  wasÂ  doneÂ  byÂ  usingÂ  MTTÂ  method and the LC50 was 268.15 Î¼M.Key words : LR-2, benzaldehyde, cytotoxic, HeLaÂ